War in the modern world since 1815 - Black, Jeremy 1955- (Warfare and history, 2003)
Conflict is central to human history. It is often the cause, course and consequence of social, cultural and political change. Military history therefore has to be more than a technical analysis of armed conflict. War in the Modern World since 1815 addresses war as a cultural phenomenon, discusses its meaning in different socities and explores the various contexts of military action.